2007
DOI: 10.1159/000098411
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Asymmetric Dimethylarginine Concentration during the Perinatal Period

Abstract: Experimental and clinical evidence has been accumulated to indicate that elevated plasma asymmetric dimethylarginine (ADMA) levels can be regarded as a marker of endothelial dysfunction that mediates cardiovascular morbidity by impairing NO-dependent vascular reactions; therefore, it may have a role in the cardiopulmonary adaptation of the neonate. The present study was undertaken to investigate the perinatal NO metabolism by measuring L-arginine, the NO synthase substrate, ADMA, the endogenous inhibitor of NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
2
17
1
Order By: Relevance
“…For ADMA and L-arginine concentrations, there were consistent veno-arterial differences, with higher levels in the umbilical vein compared with the umbilical artery, suggesting that these metabolites are mainly placentally derived, not fetally, which is consistent with a study performed in normal infants (37). ADMA and SDMA may be derived from the placenta, but may also be concentrated from the maternal plasma; it is not possible to discern between these possibilities from this study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…For ADMA and L-arginine concentrations, there were consistent veno-arterial differences, with higher levels in the umbilical vein compared with the umbilical artery, suggesting that these metabolites are mainly placentally derived, not fetally, which is consistent with a study performed in normal infants (37). ADMA and SDMA may be derived from the placenta, but may also be concentrated from the maternal plasma; it is not possible to discern between these possibilities from this study.…”
Section: Discussionsupporting
confidence: 83%
“…ADMA and SDMA may be derived from the placenta, but may also be concentrated from the maternal plasma; it is not possible to discern between these possibilities from this study. The very high concentration of ADMA in the fetal circulation is an enigma, and it has been hypothesized that it is a compensatory mechanism to stabilize very high NO concentrations in the fetoplacental unit (30,37).…”
Section: Discussionmentioning
confidence: 99%
“…Mittermayer et al [8] reported that male preterm newborns had significantly higher umbilical venous blood concentrations of ADMA than did female preterm newborns and term newborns of both sexes. Vida et al [9] reported that ADMA concentrations in umbilical blood from term newborns were elevated with a consistent venoarterial difference, suggesting that the high levels of ADMA in umbilical blood are mainly generated by the placenta. These 3 groups of investigators used HPLC for analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of ADMA concentrations in umbilical blood might be important to elucidate the regulatory mechanisms of the circulatory system in this particular period. Only 3 studies have measured umbilical blood concentrations of ADMA [7][8][9]. Asymmetric dimethylarginine in umbilical blood appears significantly higher than the maternal levels when delivery occurs at term or preterm.…”
Section: Introductionmentioning
confidence: 99%
“…In gestational diabetes, the risk continues after birth, and those women are considered to have a high risk of cardiovascular disease [28]. There is a previous study on the importance of ADMA in fetoplacental and neonatal circulation [29]. In this study, placental macro and microvascular endothelial dysfunction was established in diabetic pregnant women, but no clear information could be obtained on this subject [20,21].…”
Section: Discussionmentioning
confidence: 84%